2020
DOI: 10.3390/nu12113567
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Vitamin B12 and Global DNA Methylation in Colorectal Cancer Patients

Abstract: Vitamin B12 has been widely related to methionine metabolism, which is an essential component for biological methylation reactions, including DNA methylation. However, the relationship between vitamin B12 and DNA methylation is still controversial. In addition, there is increasing evidence for the association between vitamin B12 and the risk of colorectal cancer (CRC), although results of this association need to be assessed with caution. For this purpose, we hypothesized that serum vitamin B12 could be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Remarkably, LINE-1 methylation levels have been proposed as a biomarker of weight loss in obese subjects, influenced by dietary antioxidant capacity [ 80 ]. In our study, LINE-1 methylation was nominally associated with the availability of circulating B12, demonstrating the relevance of this vitamin for epigenetic homeostasis and genome stability, as previously hypothesized [ 81 ]. This methylation mark was not directly associated with methylation in the MTFHR gene, despite both being lower in the overweight/obese group than in the control group.…”
Section: Discussionsupporting
confidence: 83%
“…Remarkably, LINE-1 methylation levels have been proposed as a biomarker of weight loss in obese subjects, influenced by dietary antioxidant capacity [ 80 ]. In our study, LINE-1 methylation was nominally associated with the availability of circulating B12, demonstrating the relevance of this vitamin for epigenetic homeostasis and genome stability, as previously hypothesized [ 81 ]. This methylation mark was not directly associated with methylation in the MTFHR gene, despite both being lower in the overweight/obese group than in the control group.…”
Section: Discussionsupporting
confidence: 83%
“…A recent study demonstrated a higher serum B12 was associated with tumour-specific hypomethylation in CRC patients, suggestive of B12-driving epigenetic alterations leading to carcinogenesis. 34 Also, of relevance, is that vitamin b12 can be produced by the gut microbiome and that competition of b12 may affect the gut microbiome, which offers a further putative mechanistic link with colorectal cancer. 35 A possible carcinogenic effect of high serum vitamin B12 status has previously been observed in lung cancer 36 and possibly epithelial ovarian cancer, 37 but not in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The same proves true for other dietary components, such as polyphenols [ 113 ] vitamins [ 114 , 115 , 116 ], and minerals [ 116 , 117 ] alone or in combination.…”
Section: Nutrients Epigenetics and Colorectal Cancermentioning
confidence: 73%